899 Estimating the impact of weight management treatments on childhood obesity in England. (17th August 2022) - Russell, Simon; Viner, Russell
Abstract : Aims: Trials demonstrate that childhood obesity treatments are effective but to varying degrees. Some treatment programmes are less effective (e.g., lifestyle programmes), while others are deemed more effective but invasive (e.g. bariatric surgery). Yet, we know relatively little about the most effective way to implement childhood obesity treatments at a population level. That is: which children would benefit most from treatment and at what age; and at which management tier (e.g., lower tiers are low cost with greater reach, but less effective, while higher tiers are high cost with low reach, but more effective). The main aim of this work was to estimate the potential impact of weight management treatments and interventions on population prevalence and inequalities in childhood obesity in England. Methods: Using Health Survey for England data, we created a 'digital twin' of the English population and identified children with a range of weight status categories (e.g., obesity and extreme obesity), obesity comorbidities (e.g., physical and mental health conditions), and indicators of heightened risk of cardiovascular disease (e.g., blood pressure and cholesterol). Other risk factors for obesity were also identified using sociodemographic data (e.g., level of deprivation, ethnicity, income and region). Using NICE guidelines for treatment eligibility, we estimated the number of children who would be eligible for each management tier of treatment in England; where tier 1 represents interventions in primary care, tier 2 represents community interventions, tier 3 represents pharmaceutical interventions, and tier 4 represents surgical interventions. In Phase 1 of our analysis, in addition to a universal preventative intervention, we modelled a number of scenarios that represented each management tier of treatment with a range of effect sizes (based on the best available evidence) and for varying levels of uptake. We applied these scenarios individually and in combination, before comparing stepped and staged approaches. We presented Phase 1 of our analyses to a stakeholder group consisting of multi-disciplinary academics, practitioners and experts in childhood obesity treatment. Stakeholders were consulted on reasonable treatment effect sizes, levels of uptake and other model parameters in order that we could better inform our scenarios, and where there were gaps in the evidence base. Following this modified Delphi approach, we revised our assumptions and model parameters and are currently undertaking Phase 2 of our analyses. Results: Analyses from Phase 1 showed substantially higher prevalences of obesity and severe obesity, compared to other estimates across all age groups and levels of deprivation. Recent data from the National Child Measurement Programme in England suggest that these prevalences have increased following the Covid-19 pandemic. We have not reported summary findings from Phase 1 of this work here as these findings will be superseded upon completion of Phase 2. Conclusion: In this presentation, I plan to present the latest findings from Phase 2 of this work.